Overview of the international conference "Secularism as a challenge for politics and political science", 12-13 December 2019, Warsaw - Bianka Speidl (Chrześcijaństwo-Świat-Polityka)
The article discusses the conference entitled "Secularism as a challenge for politics and political science", which took place on December 12-13, 2019 at the Cardinal Stefan Wyszyński University in Warsaw.